Studies on the Coordination Behaviour of a Polydentate Schiff Base in Presence of Dimethyl Sulphoxide on Rare Earth Metal Ions - Rajendran, G.; Sreeletha, G.S (Asian Journal of Chemistry, 2010)
The present investigation is concerned with the studies on the coordination behaviour of Schiff base of pyridine-2-carboxaldehyde and 4-aminoantipyrine in presence of oxygen donor ligands such as dimethyl sulphoxide. Mixed ligand complexes of the lanthanide ions viz., La3+, Pr3+, Nd3+, Sm3+, Gd3+ and Dy3+ with Schiff base and dimethyl sulphoxide have been synthesised and characterized. The analytical data include elemental analysis, molecular weight determination, conductivity, magnetic moment, spectral, thermal and antimicrobial studies. The compositions of these complexes are found to be [Ln(P2CAAP)(DMSO)(NO3)3 where Ln = La, Pr, Nd, Sm, Gd and Dy. In these complexes the primary ligand acts as a neutral bidentate ligand; the secondary ligands viz., DMSO and the monovalent nitrate anion act as unidentate.